Analisis Pengendalian Persediaan Bahan Baku dengan Metode Economic Order Quantity (Eoq) pada Caffe Belikopi Semolowaru - Hamlatul Arsy, Awlya; Mujanah, Siti; Alifianto, Achmad Yanu (Riwayat: Educational Journal of History and Humanities, 2025)
This study was conducted to evaluate the raw material inventory management system at Belikopi Semolowaru using the Economic Order Quantity (EOQ) method. Raw material inventory is a vital aspect in maintaining smooth operational processes, but if managed inefficiently, it can lead to cost wastage and hinder production. The EOQ method was chosen because it can determine the most optimal order quantity, thereby reducing storage and ordering costs. Research data were collected through field observations, interviews with business owners, and review of raw material purchasing documents. The analysis included calculations of EOQ, safety stock, reorder point (ROP), and total inventory costs. The results showed that the implementation of EOQ at Belikopi Semolowaru was more effective than conventional methods, because it was able to reduce storage costs and reduce ordering frequency. The cost savings obtained were also more significant, thus not only increasing operational efficiency but also positively impacting the company's profitability. With more optimal inventory management, Belikopi Semolowaru was able to consistently meet customer demand without experiencing stock shortages or excess raw materials.